2010
DOI: 10.1186/1471-2350-11-82
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism rs3024505 proximal to IL-10 is associated with risk of ulcerative colitis and Crohns disease in a Danish case-control study

Abstract: BackgroundCrohns disease (CD) and ulcerative colitis (UC) are characterized by a dysregulated inflammatory response to normal constituents of the intestinal flora in the genetically predisposed host. Heme oxygenase-1 (HO-1/HMOX1) is a powerful anti-inflammatory and anti-oxidant enzyme, whereas the pro-inflammatory interleukin 1β (IL-1β/IL1B) and anti-inflammatory interleukin 10 (IL-10/IL10) are key modulators for the initiation and maintenance of inflammation. We investigated whether single nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 62 publications
1
45
1
1
Order By: Relevance
“…Therefore, in view of the abovementioned potential functional relevance of rs3024505, it is plausible to assume that C allele might increase IL10 expression causing a sustained production of IL-10 that may eventually lead to anemia in chronic inflammation present in CD patients. On the other hand, the association between C allele of rs3024505 SNP in the IL10 gene and an aggressive CD phenotype may be surprising, taking into account that this variant did not correlate with disease susceptibility in this study, as well as in other studies (Andersen et al 2010;Wang et al 2011). Our results are in contrast with the findings from New Zealand study, where individuals carrying the T allele of rs3024505 had a significantly increased risk of stricturing CD behavior (Wang et al 2011).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Therefore, in view of the abovementioned potential functional relevance of rs3024505, it is plausible to assume that C allele might increase IL10 expression causing a sustained production of IL-10 that may eventually lead to anemia in chronic inflammation present in CD patients. On the other hand, the association between C allele of rs3024505 SNP in the IL10 gene and an aggressive CD phenotype may be surprising, taking into account that this variant did not correlate with disease susceptibility in this study, as well as in other studies (Andersen et al 2010;Wang et al 2011). Our results are in contrast with the findings from New Zealand study, where individuals carrying the T allele of rs3024505 had a significantly increased risk of stricturing CD behavior (Wang et al 2011).…”
Section: Discussioncontrasting
confidence: 57%
“…The subsequent GWA studies clearly associated rs3024505 with both forms of IBD, including earlyonset UC and CD (Imielinski et al 2009;Franke et al 2010;Anderson et al 2011). The replication case-control studies that followed, found the association of T allele and TT (or CT) genotype of rs3024505 SNP with UC and/or CD in Danish, Dutch, New Zealand, Australian and North Indian IBD patients (Andersen et al 2010;Festen et al 2010;Juyal et al 2011;Doecke et al 2013;Bank et al 2014), with the exception for two studies that found no association with CD in Danish and Canadian pediatric cohorts (Amre et al 2009;Bank et al 2014). The only meta-analysis done so far, that included data from just 2 publications with 6 populations of UC patients, also associated rs3024505 with UC (Doecke et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a total of 7 case-control studies met the preset inclusion criteria, in which 1890 cases and 2929 controls were included for the pooled analysis [15][16][17][18][19][20][21] . The characteristics of the studies are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%